2019
DOI: 10.1002/ddr.21603
|View full text |Cite
|
Sign up to set email alerts
|

Novel histone deacetylase inhibitors bearing a 4‐piperidin‐4‐yl‐triazole scaffold as antitumor agents

Abstract: Histone deacetylases have proven to be promising targets for the development of anticancer drugs. In this work, we reported the design and synthesis of a series of 20 novel hydroxamic acid‐based histone deacetylase inhibitors with 4‐piperidin‐4‐yl‐triazole as the core structure. Five newly obtained compounds displayed excellent HDAC6 inhibitory activities. Among them, compounds WY‐12 and WY‐15 also exhibited excellent antiproliferative activities against six human tumor cell lines. WY‐15 could increase the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…At this step, the pursued chemical diversity was introduced by the different types of substituent on the aromatic ester. It was decorated with electron-withdrawing or -donating groups to assess the effect of electronic properties, with a special focus on the methoxy group (mono-, di-, and trimethoxy substituted), since these benzoyl derivatives (amides and esters) are privileged structural scaffolds, which are widely distributed in different anticancer and antiviral compounds. ,, Other relevant scaffolds broadly distributed in natural products with diverse and important biological functions (among them antiviral activities) are trimethoxycynnamic derivatives (esters and amides) . For the preparation of these serinol derivative esters ( 35 – 37 ), the condensation took place using carboxylic acid as acylating agent under Steglich conditions (EDCI, DMAP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this step, the pursued chemical diversity was introduced by the different types of substituent on the aromatic ester. It was decorated with electron-withdrawing or -donating groups to assess the effect of electronic properties, with a special focus on the methoxy group (mono-, di-, and trimethoxy substituted), since these benzoyl derivatives (amides and esters) are privileged structural scaffolds, which are widely distributed in different anticancer and antiviral compounds. ,, Other relevant scaffolds broadly distributed in natural products with diverse and important biological functions (among them antiviral activities) are trimethoxycynnamic derivatives (esters and amides) . For the preparation of these serinol derivative esters ( 35 – 37 ), the condensation took place using carboxylic acid as acylating agent under Steglich conditions (EDCI, DMAP).…”
Section: Resultsmentioning
confidence: 99%
“…50 , half maximal inhibitory concentration; PCR, polymerase chain reaction; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; DMSO, dimethyl sulfoxide; pTP, precursor of the terminal protein; DBP, DNA-binding protein; HCMV, human cytomegalovirus; TLC, thin layer chromatography; UV, ultraviolet; NMR, nuclear magnetic resonance spectroscopy; COSY, correlation spectroscopy;…”
mentioning
confidence: 99%
“…Besides the above-mentioned hybrids, 1,2,3-triazoleartemisinins, [97,98] 1,2,3-triazole-aziridines, [99,100] 1,2,3-triazoledithiocarbamates, [101] 1,2,3-triazole-indoles, [102] 1,2,3-triazolemollugin, [103] 1,2,3-triazole-D-(+)-pinitols, [104] 1,2,3-triazole-nerols, [105] 1,2,3-triazole-retinoids, [106] 1,2,3-triazole-salinomycin, [107] 1,2,3-triazoleethacrynic acids, [108] 1,2,3-triazole-curcumins, [109] benzotriazolehydrazones, [110] and 1,2,3-triazole-10,11-dihydro-9H-9,10- [3,4] epipyrroloanthracene-12,14(13H,15H)-diones [111] also possessed certain antileukemic activity. Amongst them, the 1,2,3-triazole-salinomycin hybrid 47 (Figure 8; IC 50 : 250 nM, MTT assay) was 2.3-and 136.8-fold more potent than salinomycin (IC 50 : 580 nM) and cisplatin (IC 50 :…”
Section: 23-triazole-naphthoquinone Hybridsmentioning
confidence: 99%
“…Besides the above‐mentioned hybrids, 1,2,3‐triazole‐artemisinins, [ 97,98 ] 1,2,3‐triazole‐aziridines, [ 99,100 ] 1,2,3‐triazole‐dithiocarbamates, [ 101 ] 1,2,3‐triazole‐indoles, [ 102 ] 1,2,3‐triazole‐mollugin, [ 103 ] 1,2,3‐triazole‐ d ‐(+)‐pinitols, [ 104 ] 1,2,3‐triazole‐nerols, [ 105 ] 1,2,3‐triazole‐retinoids, [ 106 ] 1,2,3‐triazole‐salinomycin, [ 107 ] 1,2,3‐triazole‐ethacrynic acids, [ 108 ] 1,2,3‐triazole‐curcumins, [ 109 ] benzotriazole‐hydrazones, [ 110 ] and 1,2,3‐triazole‐10,11‐dihydro‐9 H ‐9,10‐[3,4]epipyrroloanthracene‐12,14(13 H ,15 H )‐diones [ 111 ] also possessed certain antileukemic activity. Amongst them, the 1,2,3‐triazole‐salinomycin hybrid 47 (Figure 8; IC 50 : 250 nM, MTT assay) was 2.3‐ and 136.8‐fold more potent than salinomycin (IC 50 : 580 nM) and cisplatin (IC 50 : 3.42 μM) against HL‐60 leukemia cells, but the SAR revealed that 1,2,3‐triazole moiety was not essential for the high activity [ 107 ] ; the 1,2,3‐triazole‐ethacrynic acid hybrids 48a,b (IC 50 : 310 and 290 nM, MTT assay) not only were highly active against HL‐60 leukemia cells, but also were comparable to doxorubicin (IC 50 : 50.1–700 nM and 20.2–650 vs. 2.1–120 nM) against A549, MCF‐7, PC3, U87‐MG, SKOV3, and HCT‐116 cancer cell lines [ 108 ] ; the 1,2,3‐triazole‐curcumin hybrids 49a,b (IC 50 : 3.13 and 3.95 μM, MTT assay) were around three times more active than curcumin (IC 50 : 10.51 μM) against CCRF‐CEM leukemia cells, and hybrid 49a decreased mitochondrial transmembrane potential, arrested SubG0 phase and induced apoptosis [ 109 ] ; benzotriazole‐hydrazone hybrid 50 (IC 50 : 25 nM, SRB assay) was 18‐fold more potent than doxorubicin (IC 50 : 450 nM) against HL‐60 leukemia cells, and this hybrid accumulated cells in pre‐G1 phase, arrested cell cycle at G2/M phase and induced apoptosis [ 110 ] ; 1,2,3‐triazole‐10,11‐dihydro‐9 H ‐9,10‐[3,4]epipyrroloanthracene‐12,14(13 H ,15 H )‐dione hybrid 51 (IC 50 : 4.8 and 1.0 μM, MTT assay) showed promising activity against HL‐60 and its multidrug‐resistant counterpart HL60R cells, demonstrating its potential to overcome drug resistance.…”
Section: Miscellaneous 123‐triazole Hybridsmentioning
confidence: 99%